Do conteúdo à expressão: uma análise semiótica dos textos pictóricos de mestre Ataíde - Elisson Ferreira Morato (2008)
In this work, we analyze, in the light of the plastic or visual semiotics (adevelopment of Greimas semiotics or French Semiotics), five texts/canvas about Christs life produced by the Baroque painter Manoel da Costa Ataíde. The main object of our investigation is the semi-symbolism, defined as a type of significant relationship that results from the articulation between the two plans that compose the text: the content plan and the expression plan. As the semi-symbolism is an articulation of categories belonging to the two plans, our approach includes the exam of the content plan, by means of the generative course of meaning, and of the expression plan, that, in the case of painting, includes dimensions related to space, light, color and form, considering also some relevant contributions of the History of Art (as the iconographic analysis). We found in the content plan of the texts/canvas by Mestre Ataíde categories that go through the religious (Christian) speech as a whole, but that were masterfully worked by the Baroque, such as the fundamental oppositions / humanity / vs / divinity / and /death / vs / life / and themes like perdition vs salvation. Those categories of the content plan are ratified by the categories of the expression plan, located in the topological dimension (central vs outlying), the photo-chromatic dimension (clear vs dark, hot colors vs cold colors) and the eidetic dimension (dilated vs contracted), building semi-symbolic relationships that are responsible for the effects of meaning generated in/by the text. In this way, the contents of the Baroque religious speech are expressed through aesthetic elements related to painting.